HLA Class I (A and B) Allele Polymorphism in a Moroccan Population Infected with Hepatitis C Virus - Safa Machraoui; Abdelmalek Hakmaoui; Khaoula Errafii; Mehdi Knidiri; Lamiaa Essaadouni; Khadija Krati; Brahim Admou (Current Issues in Molecular Biology)
Hepatitis C virus (HCV) infection is one of the major health burdens worldwide. Its course depends on the virus itself and the host’s immune responses. The latter are conditioned by immunogenetic factors, in particular human leukocyte antigens (HLAs), whose role in determining the outcome of infection varies according to populations and ethnic groups. The current study attempted to investigate the possible relationship between HLA-A and HLA-B allele polymorphism and its impacts on the clinical outcome of HCV for a better understanding of disease susceptibility and clearance. A cross-sectional and comparative study was carried out on 40 patients with hepatitis C and 100 ethnically matched healthy control subjects originating from southern Morocco. HLA class I alleles were typed using the high-resolution PCR-SSO method. The prevalence of certain HLA class I alleles differed significantly between HCV-infected individuals and healthy controls. In particular, HLA-A*02:01 was less prevalent in chronic HCV infection (p = 0.002), indicating a potential protective effect, while the higher prevalence of HLA-A*68:02, A*66:01 B*15:03, B*41:02, B*44:03, and B*50:01 in patients could indicate a predisposing factor. These findings support the association of these immunogenetic markers with HCV infection, indicating their possible role in determining clinical and genotype forms as well as the outcome of HCV infection. Thus, an in-depth analysis of these alleles could lead to a better understanding of HCV pathogenesis and potential targeted interventions.